2020
DOI: 10.3389/fphys.2020.00989
|View full text |Cite
|
Sign up to set email alerts
|

The Enigma of Endothelium in COVID-19

Abstract: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndromerelated coronavirus-2 (SARS-CoV-2) has affected millions of people globally. Clinically, it presents with mild flu-like symptoms in most cases but can cause respiratory failure in high risk population. With the aim of unearthing newer treatments, scientists all over the globe are striving hard to comprehend the underlying mechanisms of COVID-19. Several studies till date have indicated a dysregulated host immune response as the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 62 publications
1
86
0
1
Order By: Relevance
“…Consequently, the inflammation reaches endothelial levels and then intensifies. However, it is proposed that endothelial injury is due much more to inflammatory responses from the host due to epithelium infection rather than viral replication or increased viral load in EC [ 71 ]. In summary, direct or indirect activation of EC by SARS-CoV-2 infection culminates in pulmonary edema and triggers a coagulation cascade that is implicated in severe cases of COVID-19.…”
Section: Endothelial Cells In Sars-cov-2 Infection: Inflammation Andmentioning
confidence: 99%
“…Consequently, the inflammation reaches endothelial levels and then intensifies. However, it is proposed that endothelial injury is due much more to inflammatory responses from the host due to epithelium infection rather than viral replication or increased viral load in EC [ 71 ]. In summary, direct or indirect activation of EC by SARS-CoV-2 infection culminates in pulmonary edema and triggers a coagulation cascade that is implicated in severe cases of COVID-19.…”
Section: Endothelial Cells In Sars-cov-2 Infection: Inflammation Andmentioning
confidence: 99%
“…COVID-19 ARDS (CARDS) is diagnosed when someone with confirmed COVID-19 infection meets the Berlin 2012 ARDS diagnostic criteria that consist in the presence of these features: acute hypoxemic respiratory failure, presentation within 1 week of worsening respiratory symptoms, bilateral airspace disease on CXR or CT or LUS that is not fully explained by effusions, lobar or lung collapse, or nodules, and exclusion of cardiac failure. To date, the exact mechanism of CARDS remains unclear, and it has been shown to have different findings from typical ARDS [ 169 , 173 , 174 , 175 , 176 ]. Various studies have suggested that patients with CARDS have markedly higher lung compliance than patients with typical ARDS, and CARDS has frequently been associated with pulmonary thrombotic injury [ 143 , 169 , 173 , 174 , 175 , 176 , 177 , 178 ].…”
Section: Covid-19 Complicationsmentioning
confidence: 99%
“…To date, the exact mechanism of CARDS remains unclear, and it has been shown to have different findings from typical ARDS [ 169 , 173 , 174 , 175 , 176 ]. Various studies have suggested that patients with CARDS have markedly higher lung compliance than patients with typical ARDS, and CARDS has frequently been associated with pulmonary thrombotic injury [ 143 , 169 , 173 , 174 , 175 , 176 , 177 , 178 ]. Chiumiello et al [ 177 ] showed that patients with CARDS exhibit normal pulmonary compliance with severe hypoxemia, probably sustained by a mismatch between hypoxic pulmonary vasoconstriction (HPV) and ventilation/perfusion (V/Q).…”
Section: Covid-19 Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This very organ is recognized as the primary target of SARS-CoV-2 attack and the responder to the attack. The ubiquity of changes caused by SARS-COV-2 in the endothelium contributes to the proneness of COVID-19 patients to multi-organ failure, as it is acknowledged in publications starting from Sardu et al (2020) up to the latest ( Froldi and Dorigo, 2020 ; Kaur et al, 2020 ).…”
Section: Pathophysiological Implicationsmentioning
confidence: 99%